Oblação como sentido de vida - Moreira, Adriana (2013)
What is oblation? This question appears as the moving force of this dissertation. To ask about oblation is to ask about its meaning and the meaning it had in the sacrificial ritual in the Israel of the Old Testament and what meaning it gives to the origin and the expression of sacrifice and worship in the land of the ancient civilizations. Oblation is the starting point but it is also the point of arrival. Oblation is a question but it is also the answer. Oblation is surrender but it also is receptivity. Oblation is exodus, going out of oneself to enter the sacredness of the other s terrain. Oblation is fraternity, solidarity, relationality, it is being-for-the-other, it is unconditional love, and being thus, it also becomes an eschatological sign. With the intent of delving into this comprehension the work follows in three parts. The first part permits investigating that such origin and expression took place through the worship of the earth, bloody and bloodless sacrifices and also human sacrifices. All peoples express themselves religiously. Within these expressions, are the rite and the sacrificial rites. The second part verifies that in the Old Testament the term minhah (= oblation) appears, technically used to express gifts in general. Later, the term was reserved for meaning vegetable/plant offerings. The minhah is connected with the offering of breads, incense, holocausts and sacrifices of slaughter and of communion. The ritual, which initially was celebrated popularly, with the Josiah Reform it came to be administered by the legally instituted priests. The sacrificial religious culture of the Israel of the Old Testament comes between the worship of the earth of the ancient civilizations and the sacrifice of the New Testament: the oblation of Jesus on the cross. The third part focuses on the theme of oblation. In Jesus, the oblation par excellence, we have the superiority of the priesthood, of the sacrifice and of the covenant which is established once and for all. It is the new sacrifice. And the covenant is also new, which bursts forth in a movement of continuity, rupture and overcoming. From the comprehension of the life, death and resurrection of Jesus, oblation comes to have as its theological place the human experience. Oblation is following, is listening to the will of God, is liberation, is grace, and is giving meaning of fullness of one s own life and of that of the other.